Radiological impact assessment due to background ionizing radiation around palm oil processing mills in southwestern Nigeria - Omogunloye, Olusegun Yemi; Ilori, Abiola Olawale; Abolade, Olamiposi Isaac (Journal of Asian Scientific Research, 2023)
This study assesses palm oil processing mills' background ionizing radiation exposure rate and is radiological health hazards in various communities within Southwestern Nigeria. At the height of 1.0 m, a digital Geiger Muller counter measured the radiation exposure rate in forty-three selected palm oil processing mills. The recorded background radiation exposure rates during non-working hours were below the recommended acceptable limit, while the background radiation exposure rates during the working hours were higher than 0.013 mR.h-1, the recommended permissible limit provided by the International Commission on Radiological Protection. During the working hours of the palm oil processing mills, the estimated absorbed dose rates and excess lifetime cancer risks were all greater than the recommended acceptable safety limits. The estimated values of the effective dose irradiated to various body organs and tissues due to radiation exposure and inhalation in the designated palm oil processing mills during their working and non-working hours were lower than the allowable global limit of 1.00 mSv.y-1. This study showed that the study area is radiologically polluted; nevertheless, the pollution may not produce any immediate radiation hazards to the residents of the area.